REVITALISASI NILAI-NILAI AGAMA DAN KEARIFAN LOKAL DALAM GERAKAN PENYELAMATAN DAN KELESTARIAN SUMBER DAYA ALAM SALINGKA DANAU MANINJAU SUMATERA BARAT - Jamaldi Jamaldi (Islam Realitas: Journal of Islamic and Social Studies, 2017)
Maninjau Lake which is one of the attractions in Agam Regency has been known in the world of tourism to the international level. The beauty of the lake along with twist 44 and guarded row of rows of rows, adding charm to the beauty of the lake. But lately various problems that occur related to the real condition or the beauty of the lake began to be neglected. Currently the condition of the lake is polluted in very poor condition. Various efforts have been made from the issuance of regulations, reduction efforts and community involvement in the saving of the lake. One important element is the value of religious beliefs as well as the local wisdom of the community such as the religious principles adopted, cultural values, tambos, history and traditions of the hereditary is the social capital and potential of hidden communities that need to be considered in development programs including the lake lake environmental pollution rescue movement. This effort can be done through implementing, actualizing, and revitalizing religious and cultural values which are summarized in the local wisdom of Maninjau Lake communities in solving environmental pollution problems of the lake in particular and environmental issues in general Danau Maninjau yang merupakan salah satu objek wisata di Kabupaten Agam sudah dikenal dalam dunia pariwisata sampai ke tingkat internasional. Keindahan danau diserta kelok 44 dan dijaga deretan bukit barisan, menambah pesona keelokan danau. Namun belakangan ini berbagai permasalahan terjadi terkait kondisi nyata atau keasrian danau yang mulai terabaikan. Saat ini kondisi danau tercemar dalam kondisi yang sangat memprihatinkan. Berbagai upaya telah dilakukan mulai dari penerbitan peraturan, upaya pengurangan, dan pelibatan masyarakat dalam penyelematan danau. Salah satu unsur penting adalah nilai keyakinan agama serta kearifan lokal masyarakat seperti prinsip agama yang dianut, nilai budaya, tambo, sejarah dan tradisi turun temurun merupakan modal sosial dan potensi masyarakat terpendam yang perlu dipertimbangkan dalam program pembangunan termasuk gerakan penyelamatan pencemaran lingkungan danau. Upaya ini dapat dilakukan melalui penerapan, aktualisasi, dan perevitalisasian nilai agama dan budaya yang terangkum dalam kearifan lokal masyarakat salingka Danau Maninjau dalam memecahkan persoalan pencemaran lingkungan danau khususnya dan persoalan lingkungan pada umumnya